Improving Students’ Ability in Writing using Peer Correction - Faricha Rizqi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Students’ writing anxiety leads students to have low writing skill whereas writing is undeniably crucial. This research is aimed to improve the students’ writing skill and investigate the extent to which peer correction method improves the students’ skill in writing explanation text. Peer correction is a teaching language method in which students receive feedback from their peer dealing with their writings. This method is considered as an effective teaching strategy which enables students to have enthusiasm and confidence in writing. Thirty of tenth grade students in Surakarta participated in this research. The data of this classroom action research were obtained by conducting test, observation and interview. Based on the data analyzed, it is found that the students’ writing skill on each aspect of writing is continuously improved in each cycle. This is affected by effective steps of peer correction method implemented.